Comparison of recombinant Culicoides allergens produced in different expression systems for IgE serology of insect bite hypersensitivity in horses of different origins. ... - Jonsdottir, Sigridur; Torsteinsdottir, Sigurbjorg; Svansson, Vilhjalmur; Gudbrandsson, Johannes; Stefansdottir, Sara Bjork; Mar Bjornsson, Jon; Runarsdottir, Arna; Marti, Eliane (University of Bern, 2021)
Insect bite hypersensitivity (IBH) is an allergic dermatitis of horses, an IgE-mediated reaction to Culicoides midges. Causative Culicoides spp. are not indigenous in Iceland resulting in high prevalence of IBH in horses born in Iceland and exported as compared to Icelandic horses born in a Culicoides rich environment. The aims were (i) to compare IgE levels in sera of IBH-affected horses born in Iceland (n = 47) with horses of the Icelandic breed (n = 23) and of other breeds (n = 27) born in Culicoides infested area; (ii) to investigate if barley could be a useful production system of allergens for IBH immunoassays. IgE binding in sera was tested by ELISA on two recombinant Culicoides allergens, rCul n 3 and rCul n 4, each produced in E. coli, insect cells and barley. Significantly more IgE was detected against all allergens in sera from IBH-affected compared to healthy horses. Icelandic-born Icelandic horses stand out with higher IgE levels against the allergens and higher area under the curve (AUC) on ...